Statistical abstract of the United States : 2010 - United States. Bureau of the Census. Data User Services Division; United States. Bureau of the Census. Administrative and Customer Services Division; U.S. Census Bureau (Washington, DC : U.S. Dept. of Commerce, Economics and Statistics Administration, Bureau of the Census, Data User Services Division, 2009)
A statistical reference and guide to over 250 statistical publications and sources from government and private organizations.
Issue for 1994- also called 114th- ed.; issue for 2004/2005 is a combined issue.
Adobe Acrobat format or numeric (.wk1 and .xls) files.
Also issued in print.
Some issues also available via the Internet at the Census Bureau web site. Address as of 1/6/98: http://www.census.gov/stat%5Fabstract/; current access is available via PURL.
System requirements for Windows (Acrobat version): Intel Pentium processor; Windows (2000 with Service Pack 2, Windows XP Professional or Home Edition, or Windows XP Tablet PC Edition, WIndows 2003 Server, Windows NT SP6 or 6a; 128MB RAM min., 256 MB or greater recommended, up to 90MB of available hard disk space; Microsoft Internet Explorer 5.5 or higher or Netscape 7.1 or 8.0, Firefox 1.0 or Mozilla 1.7.
System requirements for UNIX (Acrobat version): All of the following require at least 12MB of available hard-disk space, and a 32MB machine: IBM AIX 4.2.1 or later operating system, CDE 1.0 or Motif; DEC OSF/1 Version 4.0 or later; HP Series 9000 model 700 or higher, HP-UX 9.0.3 or later, and X Window X11R5 with HP-VUE or CDE 1.0 or later; Silicon Graphics IRIX 5.3 or later; LINUX Red Hat 5.1 or later (non-glibc versions) or Slackware Linux 2.0 or later (non-glibc version); or Sun Solaris 2.3 or later, Sun OpenWindows 3.0 or later, or Motif 1.2.3 or later, OpenLook 3.0 or CDE 1.0 or later, but note: Acrobat Reader will not run under SunOS or Solaris 2.0, 2.1, or 2.2.
Keywords: United States -- Statistics -- Periodicals; United States; CD-ROMs.; Periodicals; Statistics